Extension of Skopinski's approach to reduce (strain gauge) flight load measurement uncertainties. - Chedid, Marwan Maurizio (Cranfield University, 2017)
Structural Health Monitoring (SHM) is an essential technique for assessment of the integrity of ageing structures or certification of new aircraft. The SHM approach developed by Skopinski, based on conventional strain gauges, is one of the most reliable experimental methods for assessment of the structural loads experienced by lifting surfaces. This thesis concerns the extension of Skopinski’s approach to low aspect ratio wings with multiple spars. This is challenging problem, as the redundant load paths increase the complexity and difficulty in defining load equations and fitness functions. Similarly, locating, calibrating and selecting relevant strain gauges becomes more difficult. One of the new developments is a methodology for load measurement based on physical metrics and load data that is independent from the ground calibration used to generate the load equations. The concepts of Influence Coefficient Plots of Strain Gauge and of Loads Equations, were used to identify the predominant loads. The developed fitness function equations are all driven exclusively by these physical quantity parameters. Another key development was reduction of the effort required during the experimental phase achieved using distributed load data, obtained by numerical superposition of individual load cases to develop loads equations. In addition, this approach reduces the risk of damage to the flying test article and increasing the accuracy of the final results as the magnitude of the loads introduced does not need to be limited. This new framework was coded in Python including a new automated load equation computation technique, Linearised Physical Properties (LPP) and environment Loads Equation Technique Evaluator (LETE). Different search engines, including Exhaustive Search, Strain Gauge Reduction, and Genetic Algorithm, were made available for load assessment. Code validation (and performance) was performed through root mean square error evaluation in shear, bending and torsion loads using CIRA Test Data for two identical unmanned Space Vehicles, Castore and Polluce. The validation process demonstrated that loads equations developed on Castore can be applied to Polluce, as long as the SHM system design and instrumentations are the same.
PhD in Aerospace